STAGES AND RISKS OF ARTERIAL HYPERTENSION, DIFFERENCES BETWEEN STAGES - Axmedov Abbos; Aminov Azimjon; Ergashev Davlat (Journal of Science in Medicine and Life, 2024)
The word "hypertension" is translated from Latin as "excess pressure". What are the stages and levels of hypertension and how many risk factors affect its development - in detail in our article.